KEANEKARAGAMAN JENIS EKHINODERMATA DI PERAIRAN MOROTAI, MALUKU UTARA - Eddy Yusron (Jurnal Pro-Life, 2014)
Fauna Of Ekhinodermata Of Coastal Water Of Morotai Part Of South, Maluku Utara. Coastal water of Morotai is included in sub-province of North Halmahera, is recognized to have variety of invertebrate especially from group of echinoderm. The result from three location were found 22 species of echinoderm which included in 4 class which belong to Holothuroidea represented by 5 species, class of Echinoidea 6 species, class of Asteroidea 6 species and class of Ophiuroidea 5 species.